1983
DOI: 10.1051/rnd:19830601
|View full text |Cite
|
Sign up to set email alerts
|

Utero-ovarian relationships in placental mammals : role of uterus and embryo in the regulation of progesterone secretion by the corpus luteum. A review

Abstract: regulation of luteal progesterone secretion can be grouped according to three major types of uterus-embryo relationships : epitheliochorial, endotheliochorial or hemochorial placentation (see Wimsatt, 1962

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…A compromised intrauterine environment can result from either maternal or fetal disorders. Changes primarily manifest in the form of either hypoxia, infection or an imbalance of in utero development (Levasseur 1983, Reef et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…A compromised intrauterine environment can result from either maternal or fetal disorders. Changes primarily manifest in the form of either hypoxia, infection or an imbalance of in utero development (Levasseur 1983, Reef et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that prostaglandin F2a of uterine origin is the luteolytic agent responsible for regression of the corpus luteum in the cow, sow, mare and sheep (9). In the dog, however, it has been demonstrated that the uterus is not involved in the regulation of the cyclic corpus luteum (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…This transfer has been shown to exist for several hormones in cattle (6, 8, 11, 14, 15, 28). In this connection the lymphatics of the plica urogenitalis must be kept in mind (6,8,9,11,17).…”
Section: Discussionmentioning
confidence: 99%